Advances in Fetal Echocardiography: Early Imaging, Three/Four Dimensional Imaging, and Role of Fetal Echocardiography in Guiding Early Postnatal Management of Congenital Heart Disease. Issue 4 (3rd April 2013) - Rogers, Lindsay; Li, Jun; Liu, Liwen; Balluz, Rula; Rychik, Jack; Ge, Shuping
<x xml:space="preserve">Abstract</x> In this article, we review a number of topics that we believe reflect new and exciting aspects of fetal echocardiography. These new advances include early fetal cardiovascular imaging around 14 weeks, the utility of three/four dimensional imaging technology for the fetus, and finally the utility of fetal echocardiography for antenatal and perinatal care of congenital heart diseases to improve and optimize outcome. Finally, we briefly discussed future directions in fetal cardiac intervention.